Transformasi Digital pada Usaha Kecil: Studi Literatur dan Kasus RM Tapin Rasa dalam Meningkatkan Daya Tarik Pelanggan Melalui TikTok - Aditiya Kusuma; Hastin Umi Anisah; Mahdi Hidayatullah (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the implementation of digital transformation in small businesses through a case study of RM Tapin Rasa, a traditional restaurant leveraging TikTok as a marketing platform to enhance customer appeal. In the digital era, social media platforms like TikTok play a crucial role in consumer-oriented marketing strategies. With a